PENYELENGGARAAN SISTEM INFORMASI HUKUM PERUSAHAAN PADA BADAN USAHA BANK DALAM PELAKSANAAN GOOD CORPORATE GOVERNANCE - I Gusti Agung Eka Pertiwi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
Good Corporate Governance is the definitive system to regulate and control the companyto create value-added to all stakeholders. The concept can be interpreted of GoodGovernance in Indonesia. There are two things that are emphasized in this concept. First,the importance of the right of shareholders to obtain information correctly (accurately)and timely. Second, the company’s obligation to make disclosure is accurate, timely andtrasnparan to all information of corporate performance, ownership and stakeholder. Thistype of research is a kind of juridical empirical research. This study on the effectiveness ofthe law, namely Legal Information Systems Company On Enterprise Bank in ImplementingGood Corporate Governance. This study is limited to the legal aspects of good corporategovernance of banking, in particular systems company policy, in particular the company’sdecision-making system,the implementation of the decision making proces accountable,fast, and accurate, which determines the performance of bank corporate governance. GoodCorporate Governance provisions have not been able to support the banking corporategovernance, as expected, especially in terms of decision-making performance. Becausetheunavailability of adequate Legal Information System whichcan be used as abasis to organizethe decision-making process that is fast and accurate. Slowness and hesitation in makingdecisions on some banks are generally determined by the availability of Legal InformationSystems Company which is a data bank on bank policies that have been established.